Flood Vulnerability Analysis Using Multi-Criteria Spatial Assessment (MCSA): A Case Study in Makassar, Indonesia (Iraqi National Journal of Earth Science (INJES), 2026)
Floods are among the most frequent and destructive natural hazards affecting urban areas, particularly in rapidly developing cities in Southeast Asia. This study aims to assess and map flood vulnerability in Makassar City, Indonesia, using a Geographic Information System (GIS)-based Multi-Criteria Spatial Assessment (MCSA) approach. Five parameters were selected based on their contribution to flood susceptibility: slope gradient, soil type, rainfall intensity, land use and cover, and distance to rivers. Each parameter was classified into five categories and scored from 1 to 5 according to hydrological relevance and literature support. The parameters were integrated through a weighted overlay analysis in a GIS environment to produce a composite flood vulnerability map. The results show that high- and very-high-vulnerability zones are concentrated in low-lying, densely populated districts, such as Tamalanrea, Biringkanaya, and Manggala, areas with flat topography, poor drainage, and extensive impervious surfaces. Meanwhile, the eastern and southeastern regions exhibit lower vulnerability due to better topographic conditions and less urban pressure. The generated map offers a practical tool for local authorities and urban planners to guide disaster mitigation strategies, optimize infrastructure development, and promote more resilient urban planning in flood-prone areas.
Keywords: Flood vulnerability, Geographic Information System, Multi-Criteria Spatial Assessment, Makassar.